Workplace demands and resources as antecedents of jail officer perceived danger at work - Lambert, Eric G. (Journal of crime and justice, 2018)
Studies have revealed that some, but not all, jail custody officers fear workplace victimization. The job demands-resources theoretical model holds that job demands result in strain, increasing the chances of negative outcomes, such as job burnout, decreased job satisfaction, and fear of being harmed on the job. This framework also contends that job resources help reduce psychological strain, and, in turn, reduce negative outcomes, including fear of victimization at work. Survey results from 587 custody officers from a large county correctional system in Florida were analyzed in order to determine how various workplace demand and resource variables were related to perceived danger at work. Our multivariate analytical models revealed that the resource variables of instrumental communication, perceptions that infectious disease among inmates being properly handled, perceptions that inmates were properly controlled, perceptions that security was proper, and supervisor support were related to decreased perceptions of danger, while formalization (a resource variable) and role strain (a demand variable) were related to increased perceptions of danger. Overall, there was partial support for the job demands-resources model, with some variables having significant effects and others not.